An Introduction to the Short Stories of Rafael Sánchez Ferlosio (Castilla. Estudios de Literatura, 2024)
Despite the prestige as a writer and intellectual of Rafael Sánchez Ferlosio, and considering the extensive and notable bibliography that his three novels have generated (Alfanhuí; El Jarama and El testimonio de Yarfoz), his short stories have barely received attention. The set of his short stories presents unique features, in some cases close to the mimetic narration that El Jarama would exemplify, while in others it is close to the traditional tale, and in a third group, there would be the imaginative stories that are related to the saga that includes El testimonio de Yarfoz, and those that present an exotic and unknown world. Both due to its theme, as well as its narrative technique and rhetorical deployment, they are not secondary in the panorama of the Spanish contemporary short story.
Keywords: Spanish short story 20th and 21st centuries; Generation of the mid-century; Rafael Sánchez Ferlosio